Building a better rat trap: technological innovation, human capital and the Irula - Siri Terjesen (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
This case follows Sethu Sethunarayanan, Director of the non-profit Center for the De-velopment of Disadvantaged People (CDDP), which is dedicated to the improvement of the Irula tribe in rural villages of southeast India. The Irulas specialize in catching rats, an activity which provides the bulk of their income and food. Following a routine visit to a local village, Sethu recognized an opportunity for a better rat trap to aid the Irula rat catchers. With feedback from rat catchers, Sethu developed an innovative new trap. His innovation won the prestigious Global Development Marketplace award from the World Bank which provided the funding necessary to commercialize the new technology. The ventures implementation involved site visits to identify beneficiaries, health checks and treatment, preparatory workshops, factory establishment, factory training, production, womens micro-credit collectives, distribution and project evalua-tion. The case focuses on the relationship between human capital and technological entrepreneurship, considering the knowledge and skills required to commercialize technology for the rural poor and the positive impact on this greatly disadvantaged population.
Keywords: L26; O33; O; N35; 330; Human Capital; India; Innovation; Irula; Social Entrepreneurship; Technological Entrepreneurship; World Bank; Humankapital; Innovation; Unternehmer; Schädlingsbekämpfung; Technologie; Ethnische Gruppe; Ländliche Armut; Indien